2014
DOI: 10.3168/jds.2014-7902
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effects of molasses products on productivity and milk fatty acid profile of cows fed diets high in dried distillers grains with solubles

Abstract: Previous research has shown that replacing up to 5% [of dietary dry matter (DM)] corn with cane molasses can partially alleviate milk fat depression when cows are fed high-concentrate, low-fiber rations containing dried distillers grains with solubles. The primary objective of this study was to determine whether dietary molasses alters milk fatty acid (FA) profile or improves solids-corrected milk yield in the context of a more typical lactation diet. A secondary objective was to assess production responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
10
0
1
Order By: Relevance
“…In the current study, the main milk fatty acids was not affected by SC inclusion, with the exception of total trans-fatty acid (P < 0.05). The present finding is consistent with the reduction in trans-10 18:1 proportion in milk fat due to the inclusion of molasses to diets reported by Martel et al (2011) and Siverson et al (2014), who evaluated the effect of supplementing a high-concentrate and typical lactation diet, respectively.…”
Section: Milk Fatty Acid Profilessupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, the main milk fatty acids was not affected by SC inclusion, with the exception of total trans-fatty acid (P < 0.05). The present finding is consistent with the reduction in trans-10 18:1 proportion in milk fat due to the inclusion of molasses to diets reported by Martel et al (2011) and Siverson et al (2014), who evaluated the effect of supplementing a high-concentrate and typical lactation diet, respectively.…”
Section: Milk Fatty Acid Profilessupporting
confidence: 94%
“…However, feeding SC increased milk fat percentage and yield in dairy cows, which is in agreement with results obtained in previous studies (Broderick et al, 2008;Martel et al, 2011). This may be attributed to a lower proportion of total trans-fatty acid in milk fat (Table 5; Siverson et al, 2014) or alterations in rumen fermentation pattern inconsistent with the higher ruminal pH and acetate proportion for cows fed SC diet (Martel et al, 2011). Although inclusion of SC in the diet increased milk fat content with the highest mean observed for SC-SF treatment, a trend for a decrease in milk fat concentration was observed when SF was added to diets (P = 0.07); however, their interaction was not significant.…”
Section: Milk Yield and Compositionsupporting
confidence: 93%
“…The results of our research differ from the conclusions of Martel et al (2011) where corn grain was substituted by the sugarcane molasses in the rations for dairy cows in the quantity of 2.5 and 5 % DM and decrease of the milk yield by 1.9 and 5.6 % were found, respectively, with no significant effect on 4 % FCM yield. Siverson et al (2014) reported that increased content of sugarcane molasses in ration for lactating cows (from 2.9 to 5.8 % DM) had no positive effect on milk production (34.9 and 34.4 kg/day).…”
Section: Resultsmentioning
confidence: 99%
“…Obtained results differ from the conclusions of Martel et al (2011) where corn grain was replaced by sugarcane molasses in the quantity of 2.5 and 5 % DM of ration for lactating cows with determined decreased efficiency of ration DM utilization by 2.9 and 5.8 %, and reduced efficiency of protein utilization by 3.04 and 4.97 %. Siverson et al (2014) evaluated the effect of using the sugarcane molasses in concentration of 0-5.8 % DM and determined no significant effect on feed conversion for milk production. On the other hand these authors determined decreased utilization of protein with increased content of sugarcane molasses in lactating cow rations by 1.5-7.4 %.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a continuous interest in the use of sugarcane molasses in both conventional (Broderick and Radloff, 2004;Martel et al, 2011;Siverson et al, 2014) and organic (Soder et al, 2012;Brito et al, 2015Brito et al, , 2017 dairy systems in the United States. Whereas conventional dairy cows have been fed dried molasses or LM accompanied by other NSC supplements and corn silage (Broderick and Radloff, 2004;Martel et al, 2011;Siverson et al, 2014), organically certified dairy cows are typically fed LM as the sole NSC supplemental source to grass hay (Brito et al, 2015) or mixed grass-legume pasture (Soder et al, 2012;Brito et al, 2017). Previous dose-response studies resulted in inconsistent responses on DMI, milk yield and composition, and nutrient digestibility when dried or LM partially replaced high-moisture corn (Broderick and Radloff, 2004;Baurhoo and Mustafa, 2014) or GRC (Martel et al, 2011) in moderate-to high-starch diets.…”
Section: Introductionmentioning
confidence: 99%